Predictors of Type-2 Diabetes Self-Screening: The Impact of Health Beliefs Model, Knowledge, and Demographics - Alamer, Ahmed S. (International Journal of Statistics in Medical Research, 2025)
Background: Diabetes mellitus (DM) is a global health concern, and the intention to undergo diabetes self-screening among patients varies based on demographics and the Health Belief Model (HBM). Objective: This study aimed to identify the factors associated with the intention to engage in DM self-screening. Methods: This study included 404 participants with a 99% response rate. Saudi Arabian residents from the Jazan region, all diagnosed with type 2 diabetes, were enrolled. A validated, Arabic-translated, and structured questionnaire was used to collect data on demographics, family history, chronic disease status, DM knowledge, HBM constructs, and DM screening behavior. The study methods adhered to the STROBE Checklist for clear and reliable reporting. Results: The study found that 24.5% of the participants were in the 35-44 age group and 67.3% were male. Regarding education, 52.2% had university-level education and 79.7% had no family history of DM. Among the participants, 62.1% reported no chronic disease. The mean knowledge score was 6.44 (SD = 2.01). The study revealed that 56.9% of the respondents intended to engage in DM screening. Factors associated with intention included age (65 and over had lower odds), gender (females had slightly higher odds), and education (school qualification had higher odds). Family history and chronic disease status did not significantly affect intention. Among the HBM constructs, higher perceived susceptibility increased the odds, higher perceived severity decreased the odds, and perceived benefits and barriers had no significant associations with intention. Conclusions: This study provides valuable insights into the factors influencing the intention to engage in DM self-screening among diabetic patients. This understanding can guide targeted interventions to promote DM self-screening and enhance diabetes care outcomes.